Key Planning Recommendations For Logistics Multimodal Transport Institutions: Lessons Learned From Tanjung Priok Port In Indonesia - Nurullah Budisiswanto (Jurnal Indonesia Sosial Teknologi, 2023)
Logistics activities urgently require integration from both infrastructure and management aspects, while logistics activities are currently partial and the development is spread across various Ministries. Therefore, strong governance is needed to support the effective implementation of coordination and to harmonize and integrate all national logistics system development policies. The purpose of this study is to identify the actors participating in the management of the multimodal logistics transportation system, examine the challenges associated with multimodal transportation institution coordination, and determine the function of each actor in multimodal transportation. The success of multimodal transportation in Tanjung Priok’s port as the biggest port in Indonesia has been proven to be hampered due to elements of conflict of interest and adverse selection of informal institutions, according to the findings of the analysis related to the role of actors and problems related to multimodal transportation institutions at ports in Indonesia. Therefore, it is necessary to develop strategies from short to long terms, such as creating a special coordination forum or institution that is ad-hoc in nature for 2-3 years until the core problems of multimodal logistics are completed with the form of the institutional structure being structural and functional, developing a code of ethics to ensure consistent implementation of the long-term agenda, including commitments from institutional coordination of multimodal transport, and to establish permanent institutions as coordination platforms and 'network' organizations to facilitate the strategy of the 'long-term relational contract' concept where the network's focus on practical coordination should be widened and deepened to include more policy coordination until the core problems of multimodal logistics are resolved through institutional forms in the form of Constitution